2022
DOI: 10.3390/molecules27175679
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Relative Astringency of Tea Catechins and Distinct Astringent Sensation of Catechins and Flavonol Glycosides via an In Vitro Assay Composed of Artificial Oil Bodies

Abstract: Artificial oil bodies covered by a recombinant surface protein, caleosin fused with histatin 3 (a major human salivary peptide), were employed to explore the relative astringency of eight tea catechins. The results showed that gallate-type catechins were more astringent than non-gallate-type catechins, with an astringency order of epicatechin gallate > epigallocatechin gallate > gallocatechin gallate > catechin gallate > epigallocatechin > epicatechin > gallocatechin > catechin. As expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This indicated that flavanols normally exist in the form of gallic ester in the tea, and the hydrolysis of these substances under high temperature and high humidity conditions leads to the decrease of their content and the up-regulation of gallic acid (220.96–252.09%) and methyl gallic acid (234.83–280.33%) in the middle and late stage of yellowing. An in vitro assay described the astringency order as epicatechin gallate > epigallocatechin gallate > gallocatechin gallate > catechin gallate > epigallocatechin > epicatechin > gallocatechin > catechin, which testified the trans from gallate-type catechins to non-gallate-type catechins was beneficial to taste (C. T. Liu & Tzen, 2022 ). Gallic acid produced from the hydrolysis of flavanols has been associated with the enhanced umami taste and sweet of green tea infusion ( Kaneko, Kumazawa, Masuda, Henze, & Hofmann, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that flavanols normally exist in the form of gallic ester in the tea, and the hydrolysis of these substances under high temperature and high humidity conditions leads to the decrease of their content and the up-regulation of gallic acid (220.96–252.09%) and methyl gallic acid (234.83–280.33%) in the middle and late stage of yellowing. An in vitro assay described the astringency order as epicatechin gallate > epigallocatechin gallate > gallocatechin gallate > catechin gallate > epigallocatechin > epicatechin > gallocatechin > catechin, which testified the trans from gallate-type catechins to non-gallate-type catechins was beneficial to taste (C. T. Liu & Tzen, 2022 ). Gallic acid produced from the hydrolysis of flavanols has been associated with the enhanced umami taste and sweet of green tea infusion ( Kaneko, Kumazawa, Masuda, Henze, & Hofmann, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Catechins hold promise in materials science and nanotechnology; they are investigated for their role in developing bioactive coatings, films, and nanoparticles with applications in drug delivery, tissue engineering, and environmental remediation [125,126].…”
Section: Extraction Methodsmentioning
confidence: 99%
“…Meanwhile, the thickness of the emulsion is proportional to the astringency. Based on this, Liu and Tzen (2022) further investigated the astringency of the eight tea catechins utilizing AOBs, offering the possibility of their application in industry.…”
Section: Applicationsmentioning
confidence: 99%